2021
DOI: 10.1093/hmg/ddab142
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive phenotypic and functional analysis of dominant and recessiveFOXE3alleles in ocular developmental disorders

Abstract: The forkhead transcription factor FOXE3 is critical for vertebrate eye development. Recessive and dominant variants cause human ocular disease but the full range of phenotypes and mechanisms of action for the two classes of variants are unknown. We identified FOXE3 variants in individuals with congenital eye malformations and carried out in vitro functional analysis on selected alleles. Sixteen new recessive and dominant families, including six novel variants, were identified. Analysis of new and previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Three individuals ( P64 , P70 , P90 ) had variants in the FOXE3 gene (3/95 = 3%; 3/34 = 9% of positive cases), resulting in the severe ocular phenotype of complex microphthalmia and PA. P64 was one of two siblings, previously reported with a homozygous missense variant (c.232G>A p.Ala78Thr) 13 . Surprisingly, patient P70 carried a monoallelic c.960A>C stop‐loss variant, which is usually associated with milder ocular anomalies of dominant inheritance 13,32 . An undetected modifying factor in cis or in trans of the stop‐loss variant might explain the severity of his phenotype.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Three individuals ( P64 , P70 , P90 ) had variants in the FOXE3 gene (3/95 = 3%; 3/34 = 9% of positive cases), resulting in the severe ocular phenotype of complex microphthalmia and PA. P64 was one of two siblings, previously reported with a homozygous missense variant (c.232G>A p.Ala78Thr) 13 . Surprisingly, patient P70 carried a monoallelic c.960A>C stop‐loss variant, which is usually associated with milder ocular anomalies of dominant inheritance 13,32 . An undetected modifying factor in cis or in trans of the stop‐loss variant might explain the severity of his phenotype.…”
Section: Resultsmentioning
confidence: 95%
“…13 Surprisingly, patient P70 carried a monoallelic c.960A>C stop-loss variant, which is usually associated with milder ocular anomalies of dominant inheritance. 13,32 An undetected modifying factor in cis or in trans of the stop-loss variant might explain the severity of his phenotype.…”
Section: Foxe3 (Nm_0121863)mentioning
confidence: 99%
“…FOXE3 is usually associated with developmental anterior ocular anomalies, such as sclerocornea and microphthalmia [21]. One study also reported FOXE3 in intellectual disability and autism, but the underlying causes remained unknown [22]. CRB1 mutations are associated with several retinopathies, such as Leber congenital amaurosis and retinitis pigmentosa.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic screening is a useful tool for diagnosing these diseases. Sclerocornea-related genes that have been reported include FOXE3 , 59 , 60 BMP4 , 61 SOX2 , 62 RAX , 63 PAX6 , 64 NDP 64 and RAD21 . 65 These genes play critical roles in eye development and patients carrying mutations usually suffer from malformation of the eye.…”
Section: Main Textmentioning
confidence: 99%